Spilling the beans eating, cooking, reading and writing in British women's fiction, 1770-1830 - Moss, Sarah (Manchester University Press, 2009)
The study of food in literature complicates established critical positions. This title explores the relation in the context of late 18th and early 19th century women's fiction, where concerns about bodily, economic and intellectual productivity and consumption power decades of novels, conduct books and popular medicine.